2015
DOI: 10.1186/s12862-015-0543-6
|View full text |Cite
|
Sign up to set email alerts
|

Variation in NAT2 acetylation phenotypes is associated with differences in food-producing subsistence modes and ecoregions in Africa

Abstract: BackgroundDietary changes associated to shifts in subsistence strategies during human evolution may have induced new selective pressures on phenotypes, as currently held for lactase persistence. Similar hypotheses exist for arylamine N-acetyltransferase 2 (NAT2) mediated acetylation capacity, a well-known pharmacogenetic trait with wide inter-individual variation explained by polymorphisms in the NAT2 gene. The environmental causative factor (if any) driving its evolution is as yet unknown, but significant dif… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
47
1

Year Published

2017
2017
2023
2023

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 37 publications
(49 citation statements)
references
References 91 publications
1
47
1
Order By: Relevance
“…Subsistence mode of a population, which determines the exposure to different substances through dietary habit or a lifestyle, can direct and adjust the metabolism of an individual to a favorable scope and level with time [8, 52]. Diet rapidly and reproducibly alters the human gut microbiome [21] and it is a major determinant of gut microbial composition, which is different between Europe and Africa.…”
Section: Discussionmentioning
confidence: 99%
“…Subsistence mode of a population, which determines the exposure to different substances through dietary habit or a lifestyle, can direct and adjust the metabolism of an individual to a favorable scope and level with time [8, 52]. Diet rapidly and reproducibly alters the human gut microbiome [21] and it is a major determinant of gut microbial composition, which is different between Europe and Africa.…”
Section: Discussionmentioning
confidence: 99%
“…A study analysing the genetic structure of human populations living either in the Sahel belt or in surrounding African ecosystems showed that the predicted prevalence of NAT2 slow acetylation is significantly higher among pastoralists than among farmers in those regions, but also among populations living in the Sahel/Savannah belt than among those living in humid tropical and equatorial zones, irrespective of their lifestyle. Two alternative hypotheses have been proposed, both of which invoke selective pressures acting on the evolution of this specific gene (due to the dietary or the chemical environment, respectively).…”
Section: Genetic Evidence On Sahelian Populationsmentioning
confidence: 99%
“…This hypothesis holds that a slower acetylation phenotype became advantageous in the new dietary environments of food-producing populations, so that pre-existing alleles conferring a slow enzymatic activity, which were kept at low frequencies through purifying selection, would have become simultaneously positively selected in populations adopting agriculture or animal herding. 95 A study 96 analysing the genetic structure of human populations living either in the Sahel belt or in surrounding African ecosystems showed that the predicted prevalence of NAT2 slow acetylation is significantly higher among pastoralists than among farmers in those regions, but also among populations living in the Sahel/Savannah belt than among those living in humid tropical and equatorial zones, irrespective of their lifestyle. Two alternative hypotheses have been proposed, both of which invoke selective pressures acting on the evolution of this specific gene (due to the dietary or the chemical environment, respectively).…”
Section: Arylamine N-acetyltransferasementioning
confidence: 99%
“…In this context, the analysis of the Mandenka population is particularly motivating because it lives in a region where several infectious diseases are highly prevalent. In addition, although sub-Saharan African populations, which represent more than 2000 ethno-linguistic groups, 38 have been extensively studied for different genetic markers [39][40][41][42][43][44] including HLA, 29,[45][46][47][48] to our knowledge their HLA molecular variability has not been analysed so far at its greatest degree of detail, that is, the nucleotide level. In this study, we thus investigated the nucleotide polymorphism of 8 extended HLA genes in a sample of the Mandenka population by using full-gene NGS-MiSeq high-throughput sequencing.…”
Section: Introductionmentioning
confidence: 99%